RETRACTED ARTICLE: Upregulation of long non-coding RNA OGFRP1 facilitates endometrial cancer through regulating miR-124-3p/SIRT1 axis and activating PI3K/AKT/GSK-3β pathway - Yuqiong Lv; Shaorong Chen; Jingjing Wu; Ruyin Lin; Limei Zhou; Guimin Chen; Huiqing Chen; Yumin Ke (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Yuqiong Lv, Shaorong Chen, Jingjing Wu, Ruyin Lin, Limei Zhou, Guimin Chen, Huiqing Chen and Yumin Ke. (2019). Upregulation of long non-coding RNA OGFRP1 facilitates endometrial cancer by regulating miR-124-3p/SIRT1 axis and by activating PI3K/AKT/GSK-3b pathway. Artificial Cells, Nanomedicine, and Biotechnology. 47:1, 2083–2090, DOI: 10.1080/21691401.2019.1617727Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors checked their data and confirmed there are fundamental errors present. Therefore, they have agreed to the retraction of this article. The authors apologise for this oversight.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.